1991
DOI: 10.1002/sia.740170721
|View full text |Cite
|
Sign up to set email alerts
|

The structure of interfaces probed by sum‐frequency spectroscopy

Abstract: The chemistry of interfaces plays a fundamental role in adhesion. Many analytical methods, such as SIMS, XPS, AES and SEM, can be used to study surfaces after adhesive failure. Only a few techniques exist, however, for the non-destructive, in situ chemical analysis of buried interfaces. Infrared-visible sum-frequency generation (SFG) is one such technique. Shen has demonstrated recently' that infrared spectra of interfaces can be obtained by sum-frequency spectroscopy, even in the presence of bulk phases on ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The resonant contribution contains information about the orientation and population of the resonant vibrational dipole moment probed. The spectra were fit by using a procedure that follows previous Richmond group analysis, 49 based on a procedure described by Bain et al 50 This describes the origin of the χ (2) response, given as a convolution of a Lorentzian and Gaussian distribution:…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resonant contribution contains information about the orientation and population of the resonant vibrational dipole moment probed. The spectra were fit by using a procedure that follows previous Richmond group analysis, 49 based on a procedure described by Bain et al 50 This describes the origin of the χ (2) response, given as a convolution of a Lorentzian and Gaussian distribution:…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The resonant contribution contains information about the orientation and population of the resonant vibrational dipole moment probed. The spectra were fit by using a procedure that follows previous Richmond group analysis, based on a procedure described by Bain et al This describes the origin of the χ (2) response, given as a convolution of a Lorentzian and Gaussian distribution: Equation takes into account the homogeneous broadening (Γ L ) due to the natural decay of the vibrational mode probed and the inhomogeneous broadening (Γ v ) arising from the molecular environment of the mode. Each peak in the spectra was fit by using five parameters: amplitude ( A v ), phase (ψ v ), Lorentzian line width (Γ L ), peak position frequency (ω v ), and Gaussian line width (Γ v ).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Fits to spectra follow previous Richmond publications, 51 where the procedure described by Bain et al 52 fits line shapes to a convolution of a Gaussian and Lorentzian distribution (eq 1), taking into account the homogeneous broadening (Γ L ) caused by the nature of the vibrational transition as well as the inhomogeneous broadening (Γ v ) caused by the molecular environment of the detected vibrational modes. Each peak is fit to five parameters: amplitude (A v ), phase (φ v ), Lorentzian line width (Γ L ), frequency (ω v ), and Gaussian line width (Γ v ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…All spectra were taken in D 2 O and are the average of three VSF spectra taken on separate days. When appropriate, spectra were fit to a convolution of a Gaussian and a Lorentzian distribution originally described by Bain et al 49 The fitting equation, all fitting parameters, and peak assignments are shown in equation S1 and Tables S2 − S4.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%